Malay traditional spatial design functions related to its portrayal of cultural idenity at tourist destinations in Malaysia - Md Nor, Idham Hadi (2016)
Tourism has always been one of the major contributors to the economy in Malaysia. One subset of the industry that always been the front runner to promote tourism in Malaysia is culture tourism. Malaysia as a melting pot of ethnicity and culture is rich and diverse with intangible cultural resources that can be tapped and harnessed to further strengthen the growth of the tourism based economy. However not all of these cultural resources have been utilised fully by stakeholders and market players of the industry. One such resource is traditional Malay spatial design and aesthetics. Although many tourism based institutions in Malaysia adapt and adopt the design concepts, yet the degree of utilising the resource is still known by the tourism authorities as inadequate. Thus this study delves into examining these issues in one specific case study using the discipline of scenography. The methodology of the study undertaken is qualitative in nature and the main approach of research is intrinsic case study that has been hybridized to a certain extent with phenomenology and grounded theory methods. This hybridization is not only because the nature of the subject of the study but also due to the cross disciplinary approach to the research between the discipline of tourism, scenography and architecture. Kota Mahsuri has been chosen as the study site and the fieldwork at the site was undertaken within the duration of May 2014 to September 2014. The results have shown that the most common usage of the traditional Malay spatial design and aesthetics mainly revolves around façade visual forms rather than the evocatively living‟ content of the spatial function and its dramatic visual imagery‟. It is also found that the visual form that is utilised the most would revolve around the roof part section of the institution‟s buildings. Other building elements or structure that portrays Malay spatial functions and design are used sparingly and is dispersed throughout the facility. Most are used eclectically to build certain form of space that tries to function according to the intended objective but rather falls short to deliver. Even though there is lack of functional space within the institution still the response and feedback received by the tourists is majoritively positive. The tourists can still relate the cultural aspect of the institution whilst at the same time anticipate and accept the visuality as one of the main factors that moves their visitation. In conclusion of the study, it is proven the notion set by the tourism authorities in Malaysia that traditional Malay spatial design and aesthetics is one of the underutilised resources of tourism. But on the contrary even though it is underutilised the effects on tourism are still prevalent strongly. Thus it also raises questions that would be suitable for further study on the extent of implementation that would in actuality be adequate enough to be acknowledged as adequate. From the conclusion of the results also, few recommendations on improving the institution‟s capabilities in harnessing the spatial concept was also forwarded.